2017
DOI: 10.1093/nar/gkx908
|View full text |Cite
|
Sign up to set email alerts
|

SubtiWiki in 2018: from genes and proteins to functional network annotation of the model organism Bacillus subtilis

Abstract: Living cells are made up of individual parts, i.e. the genome, the proteins, the RNA and lipid molecules as well as the metabolites and ions. However, life depends on the functional interaction among these components which is often organized in networks. Here, we present the recent development of SubtiWiki, the integrated database for the model bacterium Bacillus subtilis (http://subtiwiki.uni-goettingen.de/). SubtiWiki is based on a relational database and provides access to published information about the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
294
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(306 citation statements)
references
References 16 publications
3
294
0
Order By: Relevance
“…Pooled barcoded library (two samples in biological triplicates) was sequenced in a single lane at Illumina HiSeq 2000 in 50 bp singleend regime at EMBL Genomics Core Facility (Heidelberg, Germany). Gene Ontology terms are according to SubtiWiki (Zhu and Stulke, 2018 Table EV7)] and total RNA was then extracted. Reads were aligned to the B. subtilis subsp.…”
Section: Rnaseq and Rt-qpcr Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled barcoded library (two samples in biological triplicates) was sequenced in a single lane at Illumina HiSeq 2000 in 50 bp singleend regime at EMBL Genomics Core Facility (Heidelberg, Germany). Gene Ontology terms are according to SubtiWiki (Zhu and Stulke, 2018 Table EV7)] and total RNA was then extracted. Reads were aligned to the B. subtilis subsp.…”
Section: Rnaseq and Rt-qpcr Validationmentioning
confidence: 99%
“…The scripts used for RNAseq data processing and analysis are available from https://github.com/mpre vorovsky/krasny-torpedo. Gene Ontology terms are according to SubtiWiki (Zhu and Stulke, 2018). For Figs 1C, D, 7B, EV3, and EV4 and Appendix Figs S1 and S5, the log2(fold change) gene expression values determined by DESeq2 are shown.…”
Section: Rnaseq and Rt-qpcr Validationmentioning
confidence: 99%
“…Even though B. subtilis is a well-studied organism (Zhu and Stülke, 2018), the information about the interaction between this bacterium and glyphosate as well as its potential to adapt to the herbicide is limiting. Previous studies revealed that growth of B. subtilis is inhibited by glyphosate that is due to the inhibition of the EPSP synthase (Fischer et al, 1986;Majumder et al, 1995;Selvapandiyan et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The tasA coding region is located within an operon alongside two other genes: namely sipW 56 and tapA (formerly yqxM) (Zhu & Stulke, 2018). SipW is a specialised signal peptidase that is linked with 57 removal of the signal peptide from both TasA (Stover & Driks, 1999b) and TapA (Stover & Driks, 1999a) 58 during the secretion process.…”
Section: Introduction 38mentioning
confidence: 99%